APPLICATON OF MYCORRIZA ON PLANTING MEDIA OF TWO TOMATO VARIETIES TO INCREASEVEGETABLE PRODUCTIVITY IN DROUGHT CONDITION - Kuswandi, Paramita Cahyaningrum; Sugiyarto, Lili (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
A method used for the development of dry areas/marginal lands is the improvement of soil structure and addition to the media to support the growth and development of crops. Tomatoes have the potential to be developed in marginal lands due to its high nutrition, high in demand and easy to be cultivated. One of the method used to improve planting media is the addition of microorganism such as mycorrhiza which can help the absorbtion of water and nutrition for plants. The interval of irrigation is used as a simulation of drought. This research aim was to observe the effect of mycorrhiza in the soil on the growth and development of tomato with several treatments of irrigation. The method used was the addition of 4 g of mycorrhiza per polybag (size 30x30 cm2), using Complete Randomized Design. There were 6 combinations of treatments. The treatments were : 3 interval of irrigation (every day, every 7 days and every 14 days), and 2 treatments of mycorrhiza (0 g and 4 g). There were 3 repetition for each combination of treatments. The results showed that the addition of mycorrhiza can increase significantly plant fresh and dry weight and also root length. The difference in plant height, number of branches, number of leaves, plant growth rate and percentage of infection were caused by the difference in irrigation interval. The difference in the varieties used also contribute to a difference in the percentage of infection. Further research must be made on the effect of mycorrhiza with addition of inorganic fertilizer to increase the growth and development of tomato plants in water stressed condition. Keywords: mycorriza, tomato, draught simulation